1997
DOI: 10.1044/jslhr.4005.1002
|View full text |Cite
|
Sign up to set email alerts
|

A Validity Study of an Implicit Phonological Awareness Paradigm

Abstract: The purpose of this investigation was to examine the validity of a nonsense-word-pairs paradigm as an implicit phonological awareness task. For this task one member of each nonsense-word-pair violated the rules of consonant combination in English (e.g., /integral kib/), and the other did not (e.g., /integral rib/). The subjects were required to choose the member of the pair that contained permissible consonant sequence(s). Eighty-one normally developing first- and second-graders were given the implicit phonolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…The results of the current study are also consistent with those of Lance et al (1997), who found that children with reading disability had poorer ''implicit phonological awareness.'' The current study extends Lance and colleagues' findings by using tasks where the child could not resort to a phonetic comparison of the stimulus to Standard English phonetic rules.…”
Section: Relation Of Current Findings To Previous Studies Of Implicitsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the current study are also consistent with those of Lance et al (1997), who found that children with reading disability had poorer ''implicit phonological awareness.'' The current study extends Lance and colleagues' findings by using tasks where the child could not resort to a phonetic comparison of the stimulus to Standard English phonetic rules.…”
Section: Relation Of Current Findings To Previous Studies Of Implicitsupporting
confidence: 93%
“…Results on this task were significantly correlated with results on explicit PA tasks, a multisyllabic word production task, and two reading outcome measures. Lance et al (1997) indicated, however, that implicit-level tasks such as the one they used do not require segmental knowledge per se and thus may reflect a more holistic level of phonological awareness. It is possible that participants analyzed the characteristics of the stimuli as a whole and determined that certain acoustic combinations are not plausible or not part of a linguistic experience base.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…É importante que, a partir desta pesquisa, os pesquisadores e profissionais que trabalham com avaliação cognitiva/neuropsicológica atentem para o papel dos julgamentos metamnemônicos e das estratégias e processos de controle no momento da avaliação da codificação e recuperação de informações. Tarefas como a utilizada aqui são presentes em outras áreas, como consciência fonológica, que já possui protocolos experimentais bem estabelecidos e validados (Lance, Swanson & Peterson, 1997). Caso haja interesse na construção de outras tarefas experimentais para avaliação online de habilidades metacognitivas, os resultados apresentados aqui podem servir como dados norteadores da pesquisa.…”
Section: Considerações Finaisunclassified
“…The most popular microphones which the research groups employed in lung sound studies were Sony TM ECM-77B omnidirectional electret condenser microphone [1][2][3][4][5][6][7] and Sony TM ECM-T140 [8][9][10][11][12][13], and T150 electret condenser microphones with air coupler [14][15][16][17][18]. Observing the time sequence of the cited studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], the findings were that the applications of linguistics and voice recognition at first, and then the studies related to the lung sounds were continuously employed the Sony TM ECM-77B, T140, and T150 omnidirectional microphones. Was the adoption of microphones such as Sony TM ECM-77B, T140, and T150 evaluated by the paper survey or the considerations of the lung sound characteristics?…”
Section: Introductionmentioning
confidence: 99%